2022
DOI: 10.3389/fnins.2022.854050
|View full text |Cite
|
Sign up to set email alerts
|

Does Neuroinflammation Underlie the Cognitive Changes Observed With Dietary Interventions?

Abstract: Dietary interventions, such as calorie restriction and ketogenic diet, have been extensively studied in ageing research, including in cognitive decline. Epidemiological studies indicate beneficial effects of certain dietary regimes on mental health, including mood disorders and dementia. However, randomised-controlled trials (the gold-standard of evidence-based medicine) on calorie restriction diets and the ketogenic diet have yet to show clinically convincing effects in neuropsychiatric disorders. This review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 150 publications
(196 reference statements)
0
3
0
Order By: Relevance
“…It is worth mentioning a popular dietary regimen, caloric restriction, which reduces food intake without incurring malnutrition. In fact, both the KD and caloric restriction diets are thought to act primarily through the same mechanisms as both diets result in an overall reduction in caloric intake and an increased level of circulating ketone bodies [93,105,106]. Indeed, the caloric restriction regimen represents a specific case of intermittent fasting, which is discussed below.…”
Section: Perspectivementioning
confidence: 99%
“…It is worth mentioning a popular dietary regimen, caloric restriction, which reduces food intake without incurring malnutrition. In fact, both the KD and caloric restriction diets are thought to act primarily through the same mechanisms as both diets result in an overall reduction in caloric intake and an increased level of circulating ketone bodies [93,105,106]. Indeed, the caloric restriction regimen represents a specific case of intermittent fasting, which is discussed below.…”
Section: Perspectivementioning
confidence: 99%
“…Additionally, it has been demonstrated that the ketogenic diet (KD) has comparable health advantages [ 23 , 24 , 25 , 26 ]. This low-sugar, moderate-protein, high-fat diet was recently discovered to significantly increase the life expectancy of aged mice while maintaining their physiological functions in comparison to controls [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…This low-sugar, moderate-protein, high-fat diet was recently discovered to significantly increase the life expectancy of aged mice while maintaining their physiological functions in comparison to controls [ 23 ]. As it mimicked caloric restriction, it presented similar health outcomes in terms of disease improvement through increased ketone body production [ 24 , 27 ]. These molecular breakdown products of ketones are typically known as substitutes for fuel under glucose-deprived conditions [ 28 ].…”
Section: Introductionmentioning
confidence: 99%